Peran Guru Pai Dalam Meningkatkan Akhlakul Karimah Siswa Kelas VIII SMP Negeri 5 Satu Atap Kalibening Banjarnegara - Rizal Baetulloh; Sri Haryanto; Salis Irvan Fuadi (Pusat Riset dan Inovasi Nasional, 2024)
This study attempts to define the idea of PAI teachers in enhancing moral development in students, investigate the role of PAI teachers in enhancing moral development in students based on Islamic teachings, and identify the elements that facilitate and impede the role of PAI teachers in enhancing moral development in students.This study employs a qualitative technique in conjunction with a descriptive strategy. Participatory observation, in-depth interviews with the principal, Islamic Religious Education instructors, and class VIII students were used to gather data.he study's findings suggest that instructors of Islamic Religious Education play a significant part in raising students' Akhlakul Karimah. By using interactive teaching strategies, role modeling, and a lighthearted approach, teachers can actively contribute to the formation of positive attitudes, behaviors, and Islamic values in students. In addition, instructors of Islamic Religious Education are crucial in helping students apply their religious lessons to their everyday lives. They teach pupils about Islamic moral principles, help them deal with moral dilemmas and situations, and help them appreciate the significance of Akhlakul Karimah.